Opportunities for improving the process of training of customs officers - Gancheva, Z. (Економічний вісник Донбасу, 2016)
One of the most common and effective ways to enhance the professional qualities of customs officers is their training. The article focuses on the various types, methods and forms of training that create opportunities to update and expand their knowledge and skills. The process of training of specialized customs administration officers is studied, its strengths and weaknesses are identified and on this basis, proposals for improving it are formulated. Одним із найбільш поширених і ефективних шляхів підвищення професійної майстерності співробітників митних служб є їх навчання. У статті розглядаються різні типи, методи і форми навчання,які створюють можливості для оновлення та розширення знань і навичок. Досліджено процес підготовки співробітників митної адміністрації, на підставі якого визначено їх сильні і слабкі сторони та викладаються пропозиції щодо поліпшення. Одним из наиболее распространенных и эффективных путей повышения профессионального мастерства сотрудников таможенных служб является их обучение. В статье рассматриваются различные типы, методы и формы обучения, которые создают возможности для обновления и расширения знаний и навыков. Исследован процесс подготовки сотрудников таможенной администрации, на основании которого определены их сильные и слабые стороны и излагаются предложения по улучшению.